AUTODESCRIPTIVE TEXT BY I.G. EHRENBURG AS AN OBJECT OF SEMIOTIC ANALYSIS - E. A. Zvereva (Гуманитарные и юридические исследования)
The article presents characteristics of auto-descriptive text by I. G. Ehrenburg, the analysis of which allows to solve the problem of a method of investigation of such text by means of semiotics. The observations and insights of the writer, including linguistic phenomena, form a semiotic paradigm, and semiotic analysis reveals the author's code and outlines a number of laws of autodescriptive text. This text is considered as a complex semiotic system that is created with a well-defined objective and functions in the current communication conditions.